2018
DOI: 10.1007/978-3-319-90092-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Social Search

Abstract: Today, most people find what they are looking for online by using search engines such as Google, Bing, or Baidu. Modern web search engines have evolved from their roots in information retrieval to developing new ways to cope with the unique nature of web search. In this chapter, we review recent research that aims to make search a more social activity by combining readily available social signals with various strategies for using these signals to influence or adapt more conventional search results. The chapter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 197 publications
(269 reference statements)
0
4
0
Order By: Relevance
“…The concept of social research refers to "a group of methods that depend on adopting the behavior of previous customers, in order to provide the information that current customers are looking for, the required information is often queried in the form of a question or inquiry by retrieving some units of information" (Brusilovsky et al, 2018). Using social mechanisms to search for information on the internet is kwon as social searching on social platforms.…”
Section: Social Searchmentioning
confidence: 99%
“…The concept of social research refers to "a group of methods that depend on adopting the behavior of previous customers, in order to provide the information that current customers are looking for, the required information is often queried in the form of a question or inquiry by retrieving some units of information" (Brusilovsky et al, 2018). Using social mechanisms to search for information on the internet is kwon as social searching on social platforms.…”
Section: Social Searchmentioning
confidence: 99%
“…Social search is the common name for a group of information retrieval approaches that leverage traces left behind by past users of information systems to help future users in the search process [23,25]. Unlike RSs, social search is intrinsically shaped by information-seeking behavior [13]. Displaying social information helps to enrich the search process, for example by augmenting results with social cues [24,49,65] or visualizing social links [20].…”
Section: Exploratory Searchmentioning
confidence: 99%
“…Similarly, a typical example of using social navigation in search context is the social annotation of search results in the ranked list with associated traffic [2] and social linking information [87]. These examples are reviewed in more detail in the Social Search chapter of this book [14]. A study presented in [13] has shown that it is more influential to provide social navigation support across multiple information-access pathways, including search, browsing, and information visualization.…”
Section: Integrating Social Navigation With Other Social Information mentioning
confidence: 99%